2015
DOI: 10.1002/prot.24754
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the catalytic domain of the ser/thr kinase PknA from M. tuberculosis shows an Src-like autoinhibited conformation

Abstract: Signal transduction mediated by Ser/Thr phosphorylation in Mycobacterium tuberculosis has been intensively studied in the last years, as its genome harbors eleven genes coding for eukaryotic-like Ser/Thr kinases. Here we describe the crystal structure and the autophosphorylation sites of the catalytic domain of PknA, one of two protein kinases essential for pathogen's survival. The structure of the ligand-free kinase domain shows an auto-inhibited conformation similar to that observed in human Tyr kinases of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Early work showed that PknA and PknB can cross-phosphorylate each other [8], though later data suggested unidirectional trans-phosphorylation of PknA by PknB, leading to the hypothesis that PknB regulates PknA activity [47]. Subsequent work, however, showed that PknA autophosphorylates in the mycobacterial cell and that PknA abundance is unaltered when PknB is depleted [15,48]. Our data showing limited overlap in peptides that are differentially phosphorylated in the pknA versus pknB depletion strains argue against a pathway in which PknB activates PknA.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Early work showed that PknA and PknB can cross-phosphorylate each other [8], though later data suggested unidirectional trans-phosphorylation of PknA by PknB, leading to the hypothesis that PknB regulates PknA activity [47]. Subsequent work, however, showed that PknA autophosphorylates in the mycobacterial cell and that PknA abundance is unaltered when PknB is depleted [15,48]. Our data showing limited overlap in peptides that are differentially phosphorylated in the pknA versus pknB depletion strains argue against a pathway in which PknB activates PknA.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Hence, the precise cues associated with the activation of PknA and its regulation is yet to be deciphered. The crystal structure of PknA revealed that in the absence of a bound substrate or ATP, PknA is present in an auto‐inhibited state . The availability of crystal structure is an invaluable tool for the design of design novel inhibitors that would specifically target PknA.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the salt bridge between the catalytic residue Lys41 and Glu60 in helix αC, one of the hallmarks of an ePK active state , is hindered in PknI by the side chain of Ile162 in the activation segment (Fig. A), similarly to the Src‐like autoinhibited conformation observed in another M. tuberculosis Ser/Thr kinase, PknA . Thus, the side chains of residues Lys41 and Glu60 are ca.…”
Section: Resultsmentioning
confidence: 92%